2021
DOI: 10.3390/ph15010007
|View full text |Cite
|
Sign up to set email alerts
|

Structured Waters Mediate Small Molecule Binding to G-Quadruplex Nucleic Acids

Abstract: The role of G-quadruplexes in human cancers is increasingly well-defined. Accordingly, G-quadruplexes can be suitable drug targets and many small molecules have been identified to date as G-quadruplex binders, some using computer-based design methods and co-crystal structures. The role of bound water molecules in the crystal structures of G-quadruplex-small molecule complexes has been analyzed in this study, focusing on the water arrangements in several G-quadruplex ligand complexes. One is the complex between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 136 publications
0
13
0
Order By: Relevance
“…Both NDI complexes involve two individual G4 units stacking at the 5′ G-quartet interface in a process mediated by a coordinating potassium ion. In these structures, many of the NDI side-chains are placed within the G4s groove regions, interacting through different hydrogen bonds, water bridges, and electrostatic contacts with the negatively charged phosphate groups, as previously reported for other branched fused polycyclic aromatic ligands [ 185 ].…”
Section: G4-ligand Complexes and Intermolecular Interaction Modesmentioning
confidence: 81%
See 2 more Smart Citations
“…Both NDI complexes involve two individual G4 units stacking at the 5′ G-quartet interface in a process mediated by a coordinating potassium ion. In these structures, many of the NDI side-chains are placed within the G4s groove regions, interacting through different hydrogen bonds, water bridges, and electrostatic contacts with the negatively charged phosphate groups, as previously reported for other branched fused polycyclic aromatic ligands [ 185 ].…”
Section: G4-ligand Complexes and Intermolecular Interaction Modesmentioning
confidence: 81%
“…Additionally, the length and the nature of the bi and tri side chains terminal groups, many functionalized with tertiary amine moieties fully protonated at physiological pH, boost the affinity and the binding energetics to the DNA and RNA G4 grooves ( Figure 8 A). Interestingly, several different structures found at the RCSB databank [ 192 ], evidence that these cationic groups do not directly interact with the G4 phosphates, but instead with bridging water molecules found intercalating the pairs of bases in the flexible grooves, which were shown to play important roles in G4 ligand interactions [ 185 ].…”
Section: G4-ligand Complexes and Intermolecular Interaction Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this arrangement, multiple bridging waters facilitate the polar secondary amine (at the 4-position of the quinazoline) and ethoxy group that are projecting away from the mostly non-polar cavity (Figs 4 and 5 , & S6 Fig ). Although it might seem counterintuitive that so much of the binding interaction is facilitated by water bridges, a recent assessment of high resolution DNA G4 crystal structure complexes showed that the 1 st and 2 nd shell waters play essential roles in stabilizing ligand-G4 interactions [ 86 ]. Thus, the structural insights gained from explicit solvent MD of ligand-G4 interactions and SiteMap [ 74 , 75 ] analyses are highly beneficial for future medicinal chemistry efforts.…”
Section: Discussionmentioning
confidence: 99%
“…An interdependence between the functions of biomolecules and their hydration waters is now well recognized (Chaplin, 2006;Raschke, 2006;Ball, 2008;Biedermannova ´& Schneider, 2016;Laage et al, 2017;Persson et al, 2018;Zsido ´& Hete ´nyi, 2021;Yamamoto et al, 2021). Water molecules are known to influence folding and recognition between biomolecules (Levy & Onuchic, 2006;Hummer, 2010), and they mediate DNApeptide recognition (Khesbak et al, 2011) and interactions between DNA and minor-groove binders (Nguyen et al, 2009;Wei et al, 2013;Neidle, 2021). Release of partially ordered water from the hydrated layer upon the binding of interacting partners is a source of entropic force (Leikin et al, 1993;Dunitz, 1994).…”
Section: Introductionmentioning
confidence: 99%